2022
DOI: 10.3389/fnins.2022.917987
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Nap Duration and Cognitive Functions Among Saudi Older Adults

Abstract: PurposeCurrent evidence of whether napping promotes or declines cognitive functions among older adults is contradictory. The aim of this study was to determine the association between nap duration and cognitive functions among Saudi older adults.MethodsOld adults (> 60 years) were identified from the Covid-19 vaccine center at Imam Abdulrahman Bin Faisal University, Dammam, Saudi Arabia between May and August 2021. Face-to-face interviews were conducted by a geriatrician or family physicians. Data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A review in 2021 also found that an early afternoon nap (post-lunch dip time) improved cognitive performance and work efficiency (Dutheil et al, 2021 ). Evidence from the included studies and other recent studies indicates that the effects of daytime naps might also differ in frequency and duration on depression (Jing et al, 2020 ; Xie et al, 2020 ; Lin et al, 2021 ; Alqurashi et al, 2022 ), cognitive function (Kitamura et al, 2021 ), and other health problems (Häusler et al, 2019 ). Recent large longitudinal (Li et al, 2018 ) and cross-sectional (Leng et al, 2021 ) studies suggested the detrimental effects of long naps and the beneficial effects of moderate naps on cognition.…”
Section: Discussionmentioning
confidence: 98%
“…A review in 2021 also found that an early afternoon nap (post-lunch dip time) improved cognitive performance and work efficiency (Dutheil et al, 2021 ). Evidence from the included studies and other recent studies indicates that the effects of daytime naps might also differ in frequency and duration on depression (Jing et al, 2020 ; Xie et al, 2020 ; Lin et al, 2021 ; Alqurashi et al, 2022 ), cognitive function (Kitamura et al, 2021 ), and other health problems (Häusler et al, 2019 ). Recent large longitudinal (Li et al, 2018 ) and cross-sectional (Leng et al, 2021 ) studies suggested the detrimental effects of long naps and the beneficial effects of moderate naps on cognition.…”
Section: Discussionmentioning
confidence: 98%
“…Another common sleep disturbance in the elderly is insomnia, defined as the inability to initiate or maintain sleep ( Reid et al, 2006 ). Alqurashi et al reported that in a sample of the elderly population in Saudi Arabia, cognitive decline was apparent among extended nappers (who nap >90 min per day) ( Alqurashi et al, 2022 ). Also, a recent study showed an inverted U-shaped association between sleep duration and cognitive decline in the elderly, where cognitive decline was apparent in those with insufficient (≤4 h per night) or excessive (≥10 h per night) sleep duration ( Ma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used data from magnetic resonance imaging (MRI) of the brain to predict or diagnose different neurodegenerative diseases ( Wang et al, 2018 ; Leong and Abdullah, 2019 ; Ma et al, 2020 ; Goenka and Tiwari, 2021 ; Alqurashi et al, 2022 ). Moreover, machine learning methods and graph analysis tools have been used to investigate brain functionalities using clinical biomarkers, for which these innovative approaches aid the early diagnosis of dementia ( Jeune et al, 2018 ; Bayahya et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Full details of this study were explained elsewhere ( 8 ). In brief, this was a cross-sectional community-based study conducted between July and October 2022.…”
Section: Methodsmentioning
confidence: 99%